The Role of Genetics in Domestic Research on Forestry Issues: A Text Mining Analysis - Titis Hutama Syah (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2022)
As a megadiverse country, Indonesia has plentiful genetic resources. The interest of domestic researchers in it and its relation to forestry scope is the focus of this paper. The objective is to determine the genetics aspects represented in forestry scholarly articles. Text mining analysis is carried out for the abstract articles, followed by topic modeling and trend analysis. Python libraries were used to conduct this research. Garuda website was the main source of the data collection. Natural language Toolkits (NLTK) were used to retrieve article information from Garuda. Sci-kit learn (SKLearn) of Latent Dirichlet Allocation module was used for topic modeling analysis, and pyLDAVis was used to represent it. SKLearn was also used for trending analysis. After article text retrieval, three topic clusters were found: forest diversity, products, and land use. The topics were scattered in 1966 abstract articles that were found during data retrieval. Article growth showed the quadratic pattern known after regression analysis. The trend showed the rapid growth of topics and scholars' interest, but the number of articles was low compared to the total articles on the Garuda portal.